Prediagnostic blood levels of organochlorines and risk of non‐Hodgkin lymphoma in three prospective cohorts in China and Singapore. Issue 3 (9th May 2019) - Bassig, Bryan A.; Shu, Xiao‐Ou; Sjödin, Andreas; Koh, Woon‐Puay; Gao, Yu‐Tang; Adams‐Haduch, Jennifer; Davis, Mark; Wang, Renwei; Xiang, Yong‐Bing; Engel, Lawrence S.; Purdue, Mark P.; Ji, Bu‐Tian; et al.
Abstract : Specific organochlorines (OCs) have been associated with non‐Hodgkin lymphoma (NHL) with varying degrees of evidence. These associations have not been evaluated in Asia, where the high exposure and historical environmental contamination of certain OC pesticides (e.g., dichlorodiphenyltrichloroethane [DDT], hexachlorocyclohexane [HCH]) are different from Western populations. We evaluated NHL risk and prediagnostic blood levels of OC pesticides/metabolites and polychlorinated biphenyl congeners in a case–control study of 167 NHL cases and 167 controls nested within three prospective cohorts in Shanghai and Singapore. Conditional logistic regression was used to analyze lipid‐adjusted OC levels and NHL risk. Median levels of p, p′‐dichlorodiphenyldichloroethylene (p, p′‐DDE), the primary DDT metabolite, and β‐HCH were up to 12 and 65 times higher, respectively, in samples from the Asian cohorts compared to several cohorts in the United States and Norway. An increased risk of NHL was observed among those with higher β‐HCH levels both overall (3rd vs . 1st tertile OR = 1.8, 95%CI = 1.0–3.2; p trend = 0.049) and after excluding cases diagnosed within 2 years of blood collection (3rd vs . 1st tertile OR = 2.0, 95%CI = 1.1–3.9; p trend = 0.03), and the association was highly consistent across the three cohorts. No significant associations were observed for other OCs, including p, p′‐DDE. Our findings provide support for an association between β‐HCH blood levels and NHL risk. This is a concern because substantial quantities of persistent, toxic residues of HCH are present in the environment worldwide. Although there is some evidence that DDT is associated with NHL, our findings for p, p′‐DDE do not support an association. Abstract : What's new? Organochlorines (OC) are environmentally persistent organic pollutants that have been associated with cancer risk. Here the authors conducted a prospective study of blood OC levels and risk of non‐Hodgkin lymphoma (NHL) in Asia, where high exposures and historical environmental contamination of certain OC pesticides have been reported. They find an association between risk of NHL and higher levels of β‐hexachlorocyclohexane, median levels of which were up to 65‐times higher in the Asian samples than in samples from several Western populations. These results add to the weight of evidence that environmental exposure to HCH is carcinogenic.